Bending the Rules to Play the Game: Accountability, DRG and Waiting List Scandals in Norway and Germany. (March 2015) - Neby, Simon; Lægreid, Per; Mattei, Paola; Feiler, Therese
Abstract : Diagnosis Related Groups (DRGs) are used for financial and administrative purposes in hospital systems across the world, and are combined with a series of administrative tools to increase efficiency and effectiveness. Economic dysfunctions of such systems are widely reported, but the organizational basis of this managerial tool and the implications for hospital governance are less explored. This article shows, through eight case studies, how DRGs and waiting list management create opportunities for gaming in Norway and Germany. It argues that whereas these effects are relatively similar, the way they are handled by different accountability types varies considerably between Norway and Germany. Despite similarities in gaming and accountability challenges in the single cases studied, the Norwegian and German systems seem to cope with gaming in different manners, as could be expected: The institutional context creates premises for resolving such issues that vary more with the actual governance setting than with the nature of a given case. Both systems are marked by a certain ambiguity and complexity defined by reforms history, institutional dynamics, and administrative traditions: the German legal‐oriented, Bismarckian system is as ambiguous as the Norwegian consensus‐oriented Beveridge‐type system.